Is self-esteem predictor of in-group bias and outgroup discrimination? - Jelić, Margareta (Array, 2005)
This paper focuses on the importance of groups for identity and self-esteem of every individual. Previous research has found that people are likely to evaluate their groups more positively than the groups they do not belong to. However, when the in-group feels threatened by the outgroup, or in cases of intergroup conflict, individuals not only express bias towards their in-group, but are also ready to derogate the outgroup. One important factor that needs to be taken into consideration is self-esteem. Long and Spears (1997) suggested that it is individuals with low social, but high personal self-esteem that show most intergroup bias because their personal self-esteem feels threatened by low social self-esteem. The objective of this study was to explore the impact of personal and social self-esteem on ethnic identity, in-group bias and outgroup discrimination. We hypothesised that individuals with higher social self-esteem would show higher tendency towards in-group bias as well as towards outgroup discrimination. We investigated the relationship between the mentioned variables in everyday setting, on two conflicted ethnic groups. The sample consisted of 1047 men and women, aged 13-83 years, living in the city of Vukovar, Croatia. This research highlighted the importance of social identity and social self-esteem in intergroup processes, and also indicated a possible role of personal self-esteem. In contrast to Long and Spears (1997), our results suggest that individuals with higher social self-esteem show more in-group bias and more outgroup discrimination than individuals with low social self-esteem. Results are discussed in frame of the Social Identity Theory.